ANGLOPHONE HEGEMONY IN TOURISM STUDIES TODAY - Graham M. S. Dann (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 1970)
Building on a recent co-edited work (Dann and Liebman Parrinello, 2009), this account seeks to demonstrate that tourism studies as a field has been unjustifiably dominated by English speakers. The point is illustrated firstly in terms of its four major theories that claim to have their origin in the Anglophone world of the 70s in spite of the realisation that they had their antecedents in Continental Europe of the 30s. Objective statistical measures from the electronic files of the Centre Internationalde Recherches et d’Études Touristiques (International Centre for Tourism Studies and Research) (CIRET) are then provided in order to reconfirm this linguistic dominance. These include recent data that relate to researchers, research centres, book publishers and journals. Finally a brief complementary analysis is undertaken of the subjective dimension of such hegemony by examining the phenomenon of self-reflexivity in a number of leading tourism scholars.